Mechanisms associated with carbohydrate metabolism and prognosis of degenerative diseases in rural and urban female populations of Faisalabad district - Mustafa, Mohammad Zahid; Tanveer, Zunera; Ahmad, Mushtaq; Ahmad, Irshad; Sadaf, Hina; Zaidi, Asma Nighat; Naeem, Muhammad; Abbasi, Babar Hilal Ahmad; Hameed, Tahir (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Degenerative diseases are the major non infectious diseases causing sever effects on human lives. These diseases are occurred due to the mismanagement in daily routine of life, malnutrition, and starving, impaired metabolism and carelessness practices. Two hundred healthy female subjects were selected from three towns of District Faisalabad. General characteristics of the population according to their nutritional habits including, age, body mass index(BMI), systolic blood pressure, diastolic blood pressure and glycemia were studied and similarities and differences among theses parameters were compared statistically. The average age in the rural and urban subjects was 34.38 ± 0.97 and 38.47 ± 1.48 years. The average trend of weight was almost the same in comparing populations. Systolic and diastolic blood pressure values in both populations were observed in close ranges however, the systolic blood pressure was slightly higher in urban population. On the basis of the values of expression of a particular parameter, sub populations were created to observe the correlations in each ethnic group. In the subjects of rural population increasing age was correlated with an increase in diastolic blood pressure (p=0.01), systolic blood pressure (p=0.02) and BMI (p=0.004). Similarly in subjects of urban population age was correlated with an increase in systolic blood pressure (p=0.006) diastolic blood pressure (p=0.009) and BMI (p=0.001). Systolic blood pressure above 125 mmHg is associated with the higher BMI group. In conclusion, there were similarities in the expression of few characteristics, however, there were some distinct variations too in both comparing populations.